German phrasebook & dictionary (Lonely Planet phrasebooks, 2015)
This is your handy passport to culturally enriching travels with the most relevant and useful German phrases and vocabulary for all your travel needs. Get to know your sushi from your sake, enjoy an elaborate tea ceremony with its centuries'-old conventions, and find your way elaborate transit maps; all with your trusted travel companion. With language tools in your back pocket, you can truly get to the heart of wherever you go, so begin your journey now! Get more from your trip with easy-to-find phrases for every travel situation!